COSTA FRACTURE PATIENTS WITH CLIPPING COSTAE MANAGEMENT AT THE WEST NUSA TENGGARA PROVINCIAL GENERAL HOSPITAL FOR THE PERIOD JANUARY 2021 - JUNE 2023: COSTA FRACTURE PATIENTS WITH CLIPPING COSTAE MANAGEMENT AT THE WEST NUSA TENGGARA PROVINCIAL GENERAL HOSPITAL FOR THE PERIOD JANUARY 2021 - JUNE 2023 - Rahma, Fathin Auliya; Arsatt, Maz Isa Anshori (Lombok Health And Science Journal, 2024)
Background: The ribs play a role in protecting the organs in the chest cavity. The ribs are also attached to the vertebrae to increase stability. Farktur costae occurs when there is a significant force on the costae or ribs. Costae fractures usually occur at the point of impact or posteriorly which is structurally the weakest part which at a severe rate can lead to the occurrence of flail chest. This causes pain at the fracture site, bruises, crepitations, and decreased ability to do full inspiration. With increasing morbidity and mortality rates due to costae fractures and affecting the quality of life of patients. Therefore, appropriate follow-up is needed in handling the costae fracture, which can be done surgical / operative fixation (clipping costae) more useful after nonoperative action. Method: This study is a descriptive study that uses secondary data in the form of x-ray (radiology) results and medical records of costae fracture patients at the West Nusa Tenggara Provincial General Hospital for the January 2021 – June 2023 period. Results and Conclusions: There were 19 cases of costae fractures with clipping costae management handled by NTB Provincial Hospital in the January 2021 – June 2023 period. The incidence of costae fractures is more prevalent in the age group of 45-54 years (31.58%), dominated by the male sex most patients experience multiple costae fractures with comorbidities can be pneumothorax, pulmonary contusion, hemothorax, and pleural effusion. The treatment performed on costae fracture patients is in the form of clipping costae which aims to stabilize and accelerate the healing process with minimal complications from the procedure. Operative management in the form of surgical fixation has been widely done with advantages that can reduce the number of complications due to costae fractures. Surgical fixation with clipping costae is considered a safe procedure with a very low risk of complications with satisfactory long-term results. The prognosis depends on the severity of the trauma suffered. Keywords: HD, CD